Long-term Safety and Immunogenicity of a Tetravalent Dengue Vaccine Candidate in Children and Adults: A Randomized, Placebo-Controlled, Phase 2 Study. (13th July 2020) - Sirivichayakul, Chukiat; Barranco-Santana, Elizabeth A; Rivera, Inés Esquilín; Kilbury, Jennifer; Raanan, Marsha; Borkowski, Astrid; Papadimitriou, Athanasia; Wallace, Derek
Abstract: Background: We report long-term safety and immunogenicity of Takeda's tetravalent dengue vaccine candidate (TAK-003) in healthy children and adults living in dengue-endemic areas in Puerto Rico, Columbia, Singapore, and Thailand. Methods: In part 1 of this phase 2, randomized, placebo-controlled trial we sequentially enrolled 1.5–45 year olds (n = 148) into 4 age-descending groups, randomized 2:1 to receive 2 doses of TAK-003 or placebo 90 days apart. In part 2, 1–11 year olds (n = 212) were enrolled and randomized 3:1 to TAK-003 or placebo groups. We assessed neutralizing antibody titers for the 4 dengue serotypes (DENV) up to month 36 in part 1, and symptomatic dengue and serious adverse events (SAEs) up to month 36 in both parts. Results: At month 36, seropositivity rates were 97.3%, 98.7%, 88.0% and 56.0% for DENV-1, -2, -3 and -4, respectively. Seropositivity rates varied significantly for DENV-4 according to serostatus at baseline (89.5% in seropositives versus 21.6% in seronegatives). No vaccine-related SAEs were reported. Conclusions: The trial demonstrated persistence of neutralizing antibody titers against TAK-003 over 3 years in children and adults living in dengue-endemic countries, with limited contribution from natural infection. TAK-003 was well tolerated. Clinical Trials Registration: NCT01511250 Abstract : TAK-003 was well tolerated in children and adults, with no vaccine-related SAEs. Three years after administration, TAK-003 induced persisting antibody titers, with seropositivity rates of 97%, 99%, 88%, and 56% against dengue serotypes DENV-1, DENV-2, DENV-3, and DENV-4, respectively.